Nursing practice research: A necessary factor in establishing and maintaining high nursing standards - Stojanović-Jovanović Biljana; Kekuš Divna (Association of Nurses Technicians and Midwives, 2020)
INTRODUCTION: Research in nursing today has a major impact on current and future nursing practice, forming an essential component of the educational process. OBJECTIVE: To investigate the workplace and position in which nurses are engaged after completing the specialization in clinical care, what is their level of motivation for further education in the profession and whether they follow the results of research on nursing practice by reading professional journals. To examine whether there is a difference in attitudes towards nursing research in relation to the age of the respondents. SUBJECTS AND METHODS: The research involved (N 86) nurses, clinical care specialists who completed specialist studies at the study program Clinical Care at Higher Education School of Professional Health Studies in Belgrade, until 2019. A questionnaire designed for the purposes of this research was used as an instrument. and a modified version of the Boot scale of nurses' attitudes toward research, which consists of subscales: Environmental Interest and Support, Cost-effectiveness and Benefits, and Barriers (Difficulties). RESULTS: At the level of the whole sample, the age of the respondents ranged from 24 to 59 years, on average 42 years 3 months (SD = 9 years 4 months). The largest number of respondents, 40 of them (46.5%) stated that the hospital ward was their workplace, 38 (44.2%) stated that they read only one nursing journal, 33 (38.4%) that they were quite motivated to continue education in the profession. As the age of the respondents increased, a more positive attitude towards research was recorded. CONCLUSION: Every nurse must be aware of the importance of professional development and work responsibly. The results indicate, that with the increase in the age of the respondents, a more positive attitude towards research in the domains of environmental support they have in the implementation of nursing research and the cost-effectiveness and benefits of nursing research.